Investigate the Ethnomedical Practices of Different Indigenous Communities: A literature Review - Ashebir Awoke; Beatriz Nunes Cosendey (Faculty of Engineering and Applied Science, 2025)
Ethnomedical practices have been integral to the health and cultural identity of indigenous communities worldwide, encompassing holistic approaches such as the use of medicinal plants, rituals, and traditional healing methods. This study specifically focuses on phytotherapy, the use of medicinal plants for therapeutic purposes, investigating its documentation, efficacy, and potential integration into modern healthcare systems. Using the PRISMA methodology, a comprehensive literature review was conducted on 3,851 records identified through SCOPUS. After systematic screening and eligibility assessment, 36 studies were included, emphasizing the pivotal role of plant-based remedies in addressing physical ailments while supporting emotional, spiritual, and communal well-being. These phytotherapeutic practices, deeply rooted in cultural heritage, prioritize preventive care, balance, and personalized approaches, making them particularly effective in areas with limited biomedical healthcare access. Key challenges include under-documentation, the lack of standardized preparation and dosage protocols, and integration barriers. However, the findings highlight the potential for collaboration between traditional healers and biomedical practitioners, fostering mutual enrichment and cultural sensitivity. This study concludes that phytotherapy, as a vital component of ethnomedical systems, represents an invaluable knowledge resource with the potential to complement modern healthcare by expanding treatment options, preserving indigenous heritage, and promoting sustainable integration into global healthcare frameworks. It recommends further participatory research, interdisciplinary collaboration, and capacity-building initiatives to overcome current challenges and ensure the preservation and application of these traditional practices.